Effects of high pressure on biochemical properties and structure of myofibrillar protein from Tegillarca granosa. (22nd November 2019) - Lv, Mingchun; Tan, Beibei; Yang, Rong; Xu, Anqi; Zhang, Jinjie; Xu, Dalun; Yang, Wenge
Summary: The effects of high‐pressure (HP) treatment parameters (300 MPa for 5 min, 350 MPa for 3 or 5 min and 400 MPa for 1 min) on the biochemical properties and structure of myofibrillar protein (MP) from Tegillarca granosa were investigated. The results showed that HP significantly affected the biochemical properties of MP. Under the HP treatment at 400 MPa for 1 min, the MP extraction yield was reduced from 32.21 to 18.34 mg g −1, and its surface hydrophobicity was increased from 89.29 to 104.69 µg. Ca 2+ ‐ATPase activity of MP decreased from 0.019 to 0.011 µmol (pi) mg −1 (pro) min −1, and both total and reactive sulfhydryl contents significantly declined. Furthermore, HP caused MP to undergo conformational changes. This study provides a reference data for the processing of T. granosa using HP treatment. Abstract : High pressure can significantly affected the biochemical properties and structure of myofibrillar protein from Tegillarca granosa .